Volcanic synchronisation of the EPICA-DC and TALDICE ice cores for the last 42 kyr BP - M. Severi; R. Udisti; S. Becagli; B. Stenni; R. Traversi (Climate of the Past, 2012)
The age scale synchronisation between the Talos Dome and the EPICA Dome C ice cores was carried on through the identification of several common volcanic signatures. This paper describes the rigorous method, using the signature of volcanic sulphate, which was employed for the last 42 kyr of the record. Using this tight stratigraphic link, we transferred the EDC age scale to the Talos Dome ice core, producing a new age scale for the last 12 kyr. We estimated the discrepancies between the modelled TALDICE-1 age scale and the new scale during the studied period, by evaluating the ratio R of the apparent duration of temporal intervals between pairs of isochrones. Except for a very few cases, R ranges between 0.8 and 1.2, corresponding to an uncertainty of up to 20% in the estimate of the time duration in at least one of the two ice cores. At this stage our approach does not allow us to unequivocally identify which of the models is affected by errors, but, taking into account only the historically known volcanic events, we found that discrepancies up to 200 yr appear in the last two millennia in the TALDICE-1 model, while our new age scale shows a much better agreement with the volcanic absolute horizons. Thus, we propose for the Talos Dome ice core a new age scale (covering the whole Holocene) obtained by a direct transfer, via our stratigraphic link, from the EDC modelled age scale by Lemieux-Dudon et al. (2010).